2016
DOI: 10.21649/akemu.v11i4.1079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of episiotomy on perineal lacerations in spontaneous vertex deliveries

Abstract: Objectives: To evaluate the effects of episiotomy on the frequency of perineal lacerations. Design: Cross-Sectional analytical study. Place & duration of study: Department of Gynae Obstetrics unit III. Lady willingdon Hospital Lahore. From April 1994 to March 1996. Patients & methods: 2918 women who delivered vaginally were included in the study. Only right mediolateral episiotomy incision was used in these cases. Local anaesthesia in the form of 2% Lignocain was used in all cases to infiltrate the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most rural deliveries carried out by midwives are without episiotomy. The rate of episiotomy in primigravida in teaching hospital like lady Wallington Lahore in 1990s was about 93% [5] Latest research showed that episiotomy is not protective against tears. The prevalence of 3 rd & 4 th degree perineal tear was 0.4% without episiotomy and 4.8% with episiotomy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most rural deliveries carried out by midwives are without episiotomy. The rate of episiotomy in primigravida in teaching hospital like lady Wallington Lahore in 1990s was about 93% [5] Latest research showed that episiotomy is not protective against tears. The prevalence of 3 rd & 4 th degree perineal tear was 0.4% without episiotomy and 4.8% with episiotomy [6,7].…”
Section: Introductionmentioning
confidence: 99%